Prototipe Sistem Keamanan Buka Pintu dan Jendela Menggunakan Aplikasi Telegram - Tiffany, Nivika; Bakti Zainal, Yuda; Indrayanto, Ricki; Charisma, Atik; Haz, Fauzia (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2024)
Crimes such as theft and housebreaking are serious problems related to security. This problem often occurs when the homeowner is out of town or leaving the house for a few days. Therefore, an effective security system is needed so that the house is not easily broken into and can be monitored via smartphone by the owner. To minimize the crime rate, we designed a microcontroller-based automatic door lock. This automatic system can control the solenoid door lock and function as a home security. This study aims to develop a door lock and window security system based on a microcontroller and the Internet of Things. This system utilizes RFID to open the door which is processed by Arduino, as well as a PIR Sensor for double security which is processed using NodeMCU ESP8266. The smartphone functions as a medium for monitoring and opening the door. The NodeMCU ESP8266 microcontroller on the PIR Sensor is tasked with processing data so that when the sensor detects movement, the buzzer will sound and send a notification to the smartphone. The results of the study show that the automatic door lock can be accessed via RFID and applications on smartphones. The system can detect RFID at a distance of 3 cm with a response time of 2-5 seconds, and successfully detects movement in humans and animals with an accuracy rate of 86.67%.